Hubungan Pola Asuh Orang Tua dengan Kejadian Pelecehan Seksual Verbal pada Remaja di SMKN Widang - Safira, Vonny; Ilmiatus Qoyimah; Nurus Safa’ah; Dyah Pitaloka (Inovasi Kesehatan Global, 2026)
Verbal sexual harassment among adolescents is a form of non-physical violence that is often overlooked, yet it has significant impacts on psychological health and social development. Parenting style is suspected to be one of the factors influencing adolescents' vulnerability to verbal sexual harassment. This study aims to examine the relationship between parenting styles and the occurrence of verbal sexual harassment among adolescents at SMKN Widang. This study employed a quantitative design with a cross-sectional approach. The sample consisted of 166 participants selected using a simple random sampling technique. Data were collected using questionnaires on parenting styles and verbal sexual harassment. Data analysis was conducted using the Contingency Coefficient test with a significance level of 0.05. The results showed that the majority of respondents experienced democratic parenting (70.5%). The incidence of verbal sexual harassment was most frequently reported in the “often” category (43.4%) and “sometimes” category (42.2%). Statistical analysis yielded a p-value of 0.001 (p < 0.05), indicating a significant relationship between parenting styles and the occurrence of verbal sexual harassment. Permissive parenting was associated with a relatively higher risk. Therefore, the implementation of democratic parenting and open communication is recommended as preventive efforts.